Choice preference and physical activity behaviour. (13th September 2011) - Lynch, M; Longo, A; Hutchinson, WG
Abstract : Background: Physical inactivity in addition to other influential factors has fuelled the rising level of obesity requiring greater intelligence on motivational cues for engagement in physical activity. The purpose of this study is to assess the value that respondents place on physical activity rather than consume a hypothetical medical tablet by employing Contingent Valuation (CV) and Contingent Behaviour (CB) methods. Results from this study provide constructive insight into the use value and motivations for participating in physical activity rather than avail of a substitute. Methods: The data for the study was generated by means of a self administered questionnaire completed by (n=415) respondents in Northern Ireland (NI) from January 2010 to February 2011. We combine actual minutes of physical activity with estimated minutes of physical activity and portray a hypothetical scenario should a medical tablet be available would respondents consume the tablet or do the physical activity. This medical tablet offers the same health benefits of meeting the recommended guidelines of 30 min of physical activity 5 times per week with no side effects. The authors' hypothesise that the time starved population would favour consumption of a medical tablet rather than the allocation of valuable time to engage in physical activity. Physical activity levels are self reported and to ensure certainty of responses a probing question is included to mitigate against biases. Results: Preliminary results reveal respondents' prefer to engage in physical activity opposed to the consumption of a medical tablet. The addition of the probing question indicated that respondents prefer to do physical activity for their physical and mental health in addition to a leisure activity aiding relaxation. Preference to participate in physical activity was chosen by 97% of the sample with only 3% of respondents opting for consumption of the medical tablet with respondents' willing to pay £1 for the convenience of consuming a tablet rather than engage in physical activity. Conclusion: Our results suggest that respondents' allocate substantial use value to participation in physical activity and the substitution of a time limiting alternative to engagement in physical activity is not highly valued as hypothesised by the authors. Physical activity is valued and our study suggests that individuals engage in physical activity for their physical and mental health and that physical activity is their hobby and relaxing time. These explanations provide valuable insight into the motivations for participating in physical activity and provide intuitive structure and acumen for the future development of physical activity initiatives.